Basic ICT Counseling for the Technologically Clueless Community in Purwokerto Kulon: Penyuluhan Dasar TIK untuk Masyarakat Gaptek di Purwokerto Kulon - Sulistiyasni, Sulistiyasni; Ekowati, Nur Alfi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Based on BPS data in 2022, 23.05% of the total population of Central Java do not have ICT skill (technologically clueless). It is possible that Purwokerto Kulon is included in this percentage. To reduce the number of people who are technologically clueless in Purwokerto Kulon, a basic ICT (Information and Communication Technology) counseling was held and attended by several participants from the youth and adult age groups. The counseling method used was training in the form of workshop, while the counseling material was about the introduction of computer hardware, basic computer operations, and basic internet operations and their benefits. Based on the results of the pre-test, it was found that only about 20% of the total participants had ICT skill. After participating in counseling, the post-test results showed information that 100% of them came to know and have the ICT skill.